2009
DOI: 10.1089/aid.2009.0032
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Fails to Trigger Innate Immune Factor Synthesis in Differentiated Oral Epithelium

Abstract: The oral mucosa is relatively resistant to human immunodeficiency virus type 1 (HIV-1) transmission. The mechanisms contributing to this resistance remain incompletely understood, but may include HIV-induced synthesis of innate immune factors. We used fully differentiated oral epithelium as a surrogate for the oral mucosa in vivo, exposed it to X4- and R5-tropic HIV-1 in culture, and quantified mRNA expression of six innate immune factors. Neither virus increased expression of human beta defensin 2 (hBD-2) mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Ribosomal phosphoprotein (RPO) was used as a housekeeping control gene to determine the total RNA level. PCR conditions and primer sequences for SLPI and RPO have been previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomal phosphoprotein (RPO) was used as a housekeeping control gene to determine the total RNA level. PCR conditions and primer sequences for SLPI and RPO have been previously described .…”
Section: Methodsmentioning
confidence: 99%
“…The amplification conditions were initial denaturation at 95°C for 12 min followed by 40 cycles of denaturation at 95°C for 30 s, annealing at 57–65°C for 30 s, and elongation at 72°C for 60 s. Melt curve analysis was performed to confirm that the detected signal was that of SYBR Green binding to the expected amplification product and not to the possible primer dimers. Oligonucleotide primers were designed as previously described . In initial experiments, amplification efficiency was determined for all primer pairs.…”
Section: Methodsmentioning
confidence: 99%
“…RTD1 binds directly to the C-terminal heptad repeat of HIV envelope protein gp41, blocking formation of the six helix bundle required for fusion (Gallo et al, 2006). Recently, high concentrations of RTD1 and HNP1 have been shown to down-regulate CXCR4 in PBMCs in the absence of serum (Nittayananta et al, 2009). Studies on retrocyclin-1 analogues indicate that modification of this peptide can enhance its potency against HIV in vitro , suggesting their potential use as a microbicide.…”
Section: Table 1 Effect Of Defensins On Hiv Infectionmentioning
confidence: 99%
“…Similarly, HBD2 and HBD3 are induced in normal human oral epithelium cells, even in the absence of HIV-1 replication (Quinones-Mateu et al, 2003). Interestingly, a recent study reported that both X4-and R5-tropic viruses cannot induce HBD2 gene expression in the MatTeck oral tissue model nor primary gingival epithelial cells (Nittayananta et al, 2009). Additionally, high concentrations of X4 virus HIV-1 Lai block HBD2 gene expression by 50% (Nittayananta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation